Letter (copy) : Letter to Foreign Office - McDonald, Florence
1936-09-16 FEM/KMS/16. Secretary's. 16th September, 1936, The Rt.Hon. C.R. Attlee, M.P., "Heywood", Stanmore, Middlesex. Dear Major Attlee, LETTER TO FOREIGN OFFICE. I am returning herewith the letter addressed to you from the Foreign Office, dated 4th September, 1936, which you lent to Sir Walter at the Plymouth Congress. Yours sincerely, Private Secretary. Enc. Letter. 292/946/10/99